Effect of salam [Syzygium polyanthum (Wigt) Walp.] leaves extract on the microorganism population in chicken meat and shrimp and their sensory - Ramli, Suzita; Lim, Li Yi; Samsudin, Nik Iskandar Putra; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Recently, there has been an increasing demand and interest in developing plant extracts as natural food sanitizer, owing to their antimicrobial properties. Hence, the aim of this study was to investigate the effect of salam (Syzygium polyanthum L.) leaves methanolics extract on the number of microflora on chicken meat and shrimp. Salam leaves extract at different concentrations (0.0%, 0.1%, 1.00%) and exposure times (5, and 10 min) used to treat chicken meat and shrimp by using dilution method. Result showed that the total plate count and Staphylococcus aureus had been detected in untreated chicken and shrimp samples with 6.66 ± 0.12, 8.66 ± 0.15 and 7.25 ± 0.21, 6.54 ± 0.21, respectively. However, there was no Escherichia coli, Salmonella spp. and Vibrio cholera detected in both samples. The number of total plate count (TPC) and S. aureus in chicken meat and shrimp were starting to reduce significantly at 0.01% concentration of salam leaves extract for 5 minutes of exposure time compared to initial count. There was no significantly different between exposure times. The highest reduction in number of microorganism population was at treatment with 1.0% extract for 10 min where TPC was reduced from 6.66 ± 0.12 to 0.00 ± 0.00 log10 CFU/ml, and from 8.66 ± 0.15 to 4.88 ± 0.00 log10 CFU/ml in shrimp while S. aureus reduced from 7.25 ± 0.21 to 3.88 ± 0.01 and from 6.54 ± 0.21 to 4.92 ± 0.04 in chicken and shrimp, respectively. For the sensory acceptability, overall acceptability were accepted by panellists until treatment 0.10% for 5 min and 10 min of soaking time. In conclusion, salam leaves extract might be developed as natural sanitizer for rinsing raw food materials such as chicken meat and shrimp.